2022
DOI: 10.1002/ldr.4423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topographic variations and tillage methods on gully erosion in the black soil region: A case‐study from Northeast China

Abstract: Gully erosion is considered to be a severe land degradation process around the world. The combined effects of tillage methods and topographic variation on gully erosion are poorly understood. This study investigated permanent gullies in three farmland, geomorphic areas in the black soil region of Northeastern China: low mountains and hills, tableland, and rolling hill areas. Cross-sectional measurements were used to obtain estimates of volumetric soil loss from the gullies. Digital contour maps and remote sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Therefore, in the initial stages of the implementation of conservation tillage management, it is necessary to implement appropriate drainage measures to mitigate the intensification of soil erosion, especially the development of gully erosion. In the same region, the result of Tang et al (2020Tang et al ( , 2022 indicated that tillage management significantly affects the development of ephemeral gully and CT is prone to the development of gully erosion on long, gentle hillslopes.…”
Section: Implications For Tillage Managementmentioning
confidence: 99%
“…Therefore, in the initial stages of the implementation of conservation tillage management, it is necessary to implement appropriate drainage measures to mitigate the intensification of soil erosion, especially the development of gully erosion. In the same region, the result of Tang et al (2020Tang et al ( , 2022 indicated that tillage management significantly affects the development of ephemeral gully and CT is prone to the development of gully erosion on long, gentle hillslopes.…”
Section: Implications For Tillage Managementmentioning
confidence: 99%
“…This erosion has impaired topsoil quality and leads to crop yield loss. The impact of gully erosion on SPQ may exhibit regional variations in Heilongjiang province due to considerable differences in historical farming practices: the northern (Nenjiang), middle (Hailun), and southern (Harbin) lands were reclaimed on large scales in the 1930s, 1890s, and 1860s, respectively (Nenjiang Farm History, Hailun County Records, and Bayan County Records) [25]. Therefore, it is necessary to conduct research to address the effect of these regional variations of permanent gullies on SPQ index S in order to provide region-specific recommendations for effective management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Diversely constructed terraces are a barrier that slows the water flow rate and increases water retention. In addition, the method of contouring is used for comparable purposes in various regions of Europe and China [12][13][14][15]. Vegetation on degraded lands can aid in forming plant root systems that prevent wind and water erosion by holding the soil together.…”
Section: Introductionmentioning
confidence: 99%